Emollients, education and quality of life: the RCPCH care pathway for children with eczema. (2nd November 2011) - Cox, Helen; Lloyd, Kate; Williams, Hywel; Arkwright, Peter D; Brown, Trevor; Clark, Christine; Campbell, Margaret; Gore, Claudia; Hardman, Catherine; Langford, Andrew; Lewis-Jones, Sue; Lawton, Sandra; et al.
Abstract : Objectives: The Royal College of Paediatrics and Child Health (RCPCH) Science and Research Department was commissioned by the Department of Health to develop national care pathways for children with allergies. The eczema pathway focuses on defining the competences to improve the equity of care received by children with eczema. Method: The eczema pathway was developed by a multidisciplinary working group and was based on a comprehensive review of evidence. The pathway was reviewed by a broad group of stakeholders including paediatricians, allergists, dermatologists, specialist nurses, dietician, patients' representatives and approved by the Allergy Care Pathways Project Board and the RCPCH Clinical Standards Committee. It was also reviewed by a wide range of stakeholders. Results: The results are presented in three sections: the evidence review, mapping and the core knowledge document. The various entry points to the ideal pathway of care are defined from self-care through to follow-up. There is considerable emphasis on good skin care and when allergy problems should be dealt with. The pathway algorithm and associated competences can be downloaded from http://www.rcpch.ac.uk/allergy/eczema . Conclusions: Effective eczema management is holistic and encompasses an assessment of severity and impact on quality of life, treatment of the inflamed epidermal skin barrier, recognition and treatment of infection and assessment and management of environmental and allergy triggers. Patient and family education which seeks to maximise understanding and concordance with treatment is also important in all children with eczema.